Brownfields to green fields: Realising wider benefits from practical contaminant phytomanagement strategies. (15th December 2016) - Cundy, A.B.; Bardos, R.P.; Puschenreiter, M.; Mench, M.; Bert, V.; Friesl-Hanl, W.; Müller, I.; Li, X.N.; Weyens, N.; Witters, N.; Vangronsveld, J.
Abstract: Gentle remediation options (GROs) are risk management strategies or technologies involving plant (phyto-), fungi (myco-), and/or bacteria-based methods that result in a net gain (or at least no gross reduction) in soil function as well as effective risk management. GRO strategies can be customised along contaminant linkages, and can generate a range of wider economic, environmental and societal benefits in contaminated land management (and in brownfields management more widely). The application of GROs as practical on-site remedial solutions is still limited however, particularly in Europe and at trace element (typically metal and metalloid) contaminated sites. This paper discusses challenges to the practical adoption of GROs in contaminated land management, and outlines the decision support tools and best practice guidance developed in the European Commission FP7-funded GREENLAND project aimed at overcoming these challenges. The GREENLAND guidance promotes a refocus from phytoremediation to wider GROs- or phyto-management based approaches which place realisation of wider benefits at the core of site design, and where gentle remediation technologies can be applied as part of integrated, mixed, site risk management solutions or as part of "holding strategies" for vacant sites. The combination of GROs with renewables, both in terms of biomass generation but also with green technologies such as wind and solar power, can provide a range of economic and other benefits and can potentially support the return of low-level contaminated sites to productive usage, while combining GROs with urban design and landscape architecture, and integrating GRO strategies with sustainable urban drainage systems and community gardens/parkland (particularly for health and leisure benefits), has large potential for triggering GRO application and in realising wider benefits in urban and suburban systems. Quantifying these wider benefits and value (above standard economic returns) will be important in leveraging funding for GRO application and soft site end-use more widely at vacant or underutilized sites. Highlights: Gentle Remediation Options (GROs) are evaluated as practical risk management methods. Outputs and case studies are presented from the GREENLAND EC FP7 project. Data are drawn from long-term (>5 years duration) GRO field trials across Europe. GROs can effectively manage site contaminant risk while delivering wider benefits.